Evaluasi Kebijakan Pembangunan Bidang Ketahanan Pangan (Studi Kasus Pada Sektor Pertanian Tanaman Pangan Di Provinsi Jawa Barat - AndariÂ , Rosita Novi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2014)
This study aims to determine how the outcomes (ejects) of development policy in the ï¬eld of food security sector of Food Crops in West lava Province. This study used a qualitative approach to data collection techniques through desk research and qualitative descriptive data analysis. The results showedthat the impact of development policies in food security in West lava Province consisb of the ï¬rst , the physical ejjicts : decreased utilization of agricultural land (paddy) and utilization of agricultural infrastructure, npecially the activities of Land and Water ( PM ). Second, thesocio-economic impact : (1 ) increasing agricultural production togroupcrops, fruits, ornamental and medicinal plants while for rioe and vegetables tend to go up and down, ( 2 ) decrease in the percentage ofresidents who work in the agricultural sector (2008-2011 ) and then increased again in 2012, (3) increasing theincomeofï¬zrmers ingeneral, (4) the low priority the achievement of food security in West lava province when compared with the national average. Based on this, the policy recommendations of the implementation of development policies in food security policy is to continue to support the achievement of optimal results and reformulate other policies that have not been optimized as an increase in agricultural land management programs and agricultural infrastructure, agricultural human resource development programs , and social welfare programs ï¬zrmers.